Harvest Timing Affects Switchgrass Production, Forage Nutritive Value, and Nutrient Removal. Issue 4 (1st July 2013) - Kering, Maru K.; Guretzky, John A.; Interrante, Sindy M.; Butler, Twain J.; Biermacher, Jon T.; Mosali, Jagadeesh
ABSTRACT: Switchgrass ( Panicum virgatum L.) has potential for both bioenergy and forage. The objectives of this experiment were to (i) determine whether switchgrass could be harvested for greater nutritive value during the vegetative stage relative to early reproductive growth (boot stage); (ii) compare biomass yields of switchgrass harvested once vs. twice per year for bioenergy; and (iii) examine effects of N fertilizer rates on harvest systems. The experiment was a randomized complete block design with a split‐plot arrangement of harvest system treatments as main plot (harvest once per year after frost, harvest twice per year first at vegetative or boot stage, and regrowth after frost) and N fertilizer rate as subplots (0, 90, 180, and 270 kg N ha −1 ). Biomass yield was greatest and nutrient concentrations were least in the one‐cut system. For the two‐cut system, nutritive values and yields were similar. Total annual biomass increased linearly with N fertilization. Across N rates, crude protein (CP) concentration for the two‐cut systems was 50% greater (71 g kg −1 ) and acid detergent fiber (ADF) and neutral detergent fiber (NDF) concentrations were 20% lesser (465 and 856 g kg −1, respectively) than switchgrass in the one‐cut system. –Switchgrass harvested at vegetative through boot stage and its regrowth could provide forage of acceptable nutritive value to beef cows. However, greater nutrient removal requires appropriate soil fertility evaluation and fertilizer management for sustainable yields.